Manajemen Pengawasan dalam Meningkatkan Kinerja Sekolah Menengah Atas Negeri 2 Kulisusu Kabupaten Buton Utara - Hasty Hasty; Syamsul Alam; Obed Bida (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
Supervision management is an effort to manage supervisory activities in order to improve organizational performance. Thus efforts to improve school performance can be pursued by improving the quality of supervisory management. This study was conducted to analyze supervisory management in improving school performance at SMAN 2 Kulisusu, North Buton Regency using qualitative methods. Informants in this study amounted to 9 people consisting of 8 school elements, 1 supervisor element selected by using purposive sampling technique. The data collected was then analyzed descriptively to obtain an overview of Supervisory Management and School Performance through Teacher Performance and Principal Performance. The results showed that the supervisory management carried out by SMAN 2 Kulisusu supervisors in improving school performance at SMAN 2 Kulisusu had not run optimally due to limited facilities and infrastructure that were not in accordance with needs, as well as limited operational budget supervision which led to revision activities to improve program actualization results. control cannot be carried out. In addition, the supervision stage also does not run optimally, especially at the implementation stage of supervision due to the low understanding of teachers on textual supervisor instructions and the low intensity of supervisory meetings with school principals.